2021
DOI: 10.1186/s12941-021-00467-2
|View full text |Cite
|
Sign up to set email alerts
|

The face of hypervirulent Klebsiella pneumoniae isolated from clinical samples of two Iranian teaching hospitals

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp) has emerged as a pathogen of global concern. In this study, both phenotypic and genotypic tests were used to detect hvKp. Antimicrobial resistance profiles and clonal relatedness of clinical isolates were also determined. We found that 34.2% (163/477) of the isolates were tellurite resistant, and among them 102 hvKp isolates detected with iucA or iutA or peg-344 as molecular markers. The blaSHV (80.4%), followed by blaCTX-M-15 (76.5%) and blaTEM (67.6%), blaOXA-48 (53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
7
25
2
Order By: Relevance
“…Moreover, the emergence of MDR hvKp isolates has been reported, including resistance to colistin, which is used as one of the last-line antibiotics during Gram-negative bacterial infection management ( 17 ). In contrast, a few studies have shown less uptake of resistance genes by hvKp isolates due to the presence of an increased number of capsular genes ( 18 ). A study by Shankar et al from India compared health care-associated and community-acquired hvKp isolates and showed more susceptibility against all beta-lactam antibiotics and absence of most of the AMR genes ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the emergence of MDR hvKp isolates has been reported, including resistance to colistin, which is used as one of the last-line antibiotics during Gram-negative bacterial infection management ( 17 ). In contrast, a few studies have shown less uptake of resistance genes by hvKp isolates due to the presence of an increased number of capsular genes ( 18 ). A study by Shankar et al from India compared health care-associated and community-acquired hvKp isolates and showed more susceptibility against all beta-lactam antibiotics and absence of most of the AMR genes ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, ESBLs were identified in all hypervirulent strains and their carriage by hypervirulent stains were significantly higher compared to the classical ones [ 42 ]. In addition, Sanikhani et al [ 43 ] reported the prevalence rate of 21.38% among 477 K . pneumoniae clinical isolates with high percentage of MDR and high-level resistance to imipenem.…”
Section: Discussionmentioning
confidence: 99%
“…Then 300 μl of this potassium tellurite solution was added to 100 ml of Mueller–Hinton agar medium, which was autoclaved and cooled to 45–50°C. Finally, we poured it into sterile plates and examined the colonies after overnight incubation at 37°C ( Sanikhani et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%